A construção do plano individual de atendimento (PIA) nas medidas de internação no CEDUC em Mossoró – Rio Grande do Norte - Freitas, Bruna Saldanha Vieira Alves de (Universidade Federal Rural do Semi-Árido, 2017)
The present study had as objective to verify how has been the elaboration of the Individual Plan of Attendance (IPA) in the measures of internment in the CEDUC in Mossoró, Rio Grande do Norte, considering the normative parameters in force. In order to do so, was made a historical approach taken on juvenile criminal responsibility, following the legislation in force in Colonial Brazil. The emergence of doctrine of integral protection was then studied, based on Article 227 of the Federal Constitution of 1998. Subsequently,the appearance of the Estatuto da Criança e do Adolescente (ECA) was explored and its repercussions on the rights of children and adolescents. Then, the context of the appearance of Law 12,594 / 2012 (National System of Socio-Educational Assistance) was analyzed, focusing on the definition of the IPA within the scenario of implementation of the measure of internment. Subsequently, the aspects relevant to the construction of the PIA were presented, highlighting the concepts of service unit and multi-professions team. For that, the works of the authors Mário Luiz Ramidoff, João Batista da Costa, Paulo de Tarso Vannuchi, Carmem Silveira de Oliveira, Eva Maria Lakatos, Christian Laville, Jean Dionne, among others, were used as references. In addition, legislation relevant to the topic of child and adolescent protection were used, as well as scientific articles from researchers such as Flávio Américo Frasseto, Maria de Lourdes Trassi Teixeira, Selma Sauerbronn and others. Then, the reality of the preparation of PIAs in the Centro de Educação de Mossoró (CEDUC), Rio Grande do Nortewas sought to know, verifying how this instrument has been empirically constructed within this service unit. Therefore, visits were made to the CEDUC in Mossoró, in order to gather information and impressions about the object of this research, using a semi-structured interview with the technical team, as well as the study of some PIAs of adolescents of the unit under analysis. In view of this, there were some deficiencies in the preparation of the PIA in the Mossoró/RN CEDUC, as well as discrepancies, especially in relation to Law 12,594/2012 and to FUNDAC/RN Ordinance no. 270/15-GP. Finally, some suggestions for improving the application of the PIA within the public policy of socio-education were presented.
Monografia
Keywords: Direitos da criança e dos adolescentes; Plano individual de atendimento (PIA); Política pública da socioeducação; Centro educacional (CEDUC) do município de Mossoró/RN; Rights of children and adolescents; Plano individual de atendimento (PIA); Public policy of socioeducation; Centro educacional (CEDUC) of municipality of Mossoró / RN; CIENCIAS SOCIAIS APLICADAS::DIREITO